Oscillation Criteria of Solutions of Third Order Neutral Integro-Differential Equations - Abed, Taghreed Hussein; Ketab, Sattar Naser; Mohamad, Hussain Ali (Iraqi Journal of Science, 2021)
Some necessary and sufficient conditions are obtained that guarantee the oscillation of all solutions of two types of neutral integro-differential equations of third order. The integral is used in the sense of Riemann-Stieltjes. Some examples were included to illustrate the obtained results